PERAN KEGIATAN MANAQIB DALAM PEMBENTUKAN KARAKTER ISLAMI DI PONDOK PESANTREN FAJAR DUNIA - Septian Kurniawan; Akmal Rizki Gunawan; Yoyo Hambali (Turats, 2023)
This study focuses on the role of manaqib activities in the formation of Islamic character inthe Fajar Dunia Islamic Boarding School. The purpose of this study was to determine the role ofManaqib Syaikh Abdul Qadir Al-Jailani's activities in the formation of Islamic character as well. Tofind out the results of the character of the Fajar Dunia Islamic Boarding School students afterparticipating in the activities of Manaqib Syaikh Abdul Qadir Al-Jailani. The method used isdescriptive qualitative research method with the type of case study research using observation,interviews, documentation. Analysis of the data used by researchers to discuss the problem of thisresearch is a descriptive analysis technique. The data that has been obtained is collected, thenprocessed into a picture and problem, analyzed and compared with the scientific theory being studied.The role of manaqib activities is influential in the formation of Islamic character, because in manaqibactivities which contain religious spiritual activities that play a role in shaping the character of thestudents and the congregation who participated in manaqib activities. And Manaqib activities are themain attraction in terms of religious spirituality, especially for people in Indonesia. because inmanaqib he conveys stories of pious people who can be expected to be imitated or implemented bystudents and congregations.